2022
DOI: 10.3390/antiox11020225
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species in Plants: From Source to Sink

Abstract: Reactive oxygen species (ROS, partial reduction or derivatives of free radicals) are highly reactive, dangerous and can cause oxidative cell death. In addition to their role as toxic by-products of aerobic metabolism, ROS play a role in the control and regulation of biological processes such as growth, the cell cycle, programmed cell death, hormone signaling, biotic and abiotic stress reactions and development. ROS always arise in plants as a by-product of several metabolic processes that are located in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
159
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(163 citation statements)
references
References 99 publications
2
159
0
2
Order By: Relevance
“…ROS is an entirely unnecessary byproduct of metabolites and plays an important role in many biological mechanisms [ 31 ]. However, it must be accurately captured.…”
Section: Correlation Between Oxidative Stress Antioxidants and Btmentioning
confidence: 99%
“…ROS is an entirely unnecessary byproduct of metabolites and plays an important role in many biological mechanisms [ 31 ]. However, it must be accurately captured.…”
Section: Correlation Between Oxidative Stress Antioxidants and Btmentioning
confidence: 99%
“…Extreme alkalinity can bring several harmful effects in plants at the cellular level i.e.accumulation of high Na, increased ionic stress, osmotic stress bystirring up the water deficit, and eventually ensuing elevated assembly of reactive oxygen species (ROS) and oxidative (Kaiwen et al, 2020). To handle the alkali stress-induced oxidative damage, plant cells trigger endogenous antioxidant protection mechanisms likeenzymatic antioxidants (ascorbate peroxidase, catalase, peroxidase, polyphenol oxidase, superoxide dismutase) and non-enzymatic antioxidant metabolites (Mansoor et al, 2022) to counteract the adverse salt-alkaline conditions (Guo et al, 2015). Metabolic disorders caused by accumulated ROS in cells that disturb normal physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that redox reaction is very important to the biocontrol activity of plant pathogen by rhizobacteria ( Husson, 2013 ). This they do by generating reactive oxygen species (ROS) in the plant, and this serves as an antagonistic response of the plant to the pathogen and indirectly stresses the pathogen ( Qi et al, 2018 ; Mansoor et al, 2022 ). Hydrogen peroxide and other signals like salicyclic and glutathione have been observed to increase the resistance of plants to pathogens ( Herrera-Vásquez et al, 2015 ; Romero-Puertas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%